2020
DOI: 10.1186/s12984-020-00722-1
|View full text |Cite
|
Sign up to set email alerts
|

Timing-dependent effects of transcranial direct current stimulation with mirror therapy on daily function and motor control in chronic stroke: a randomized controlled pilot study

Abstract: Background: The timing of transcranial direct current stimulation (tDCS) with neurorehabilitation interventions may affect its modulatory effects. Motor function has been reported to be modulated by the timing of tDCS; however, whether the timing of tDCS would also affect restoration of daily function and upper extremity motor control with neurorehabilitation in stroke patients remains largely unexplored. Mirror therapy (MT) is a potentially effective neurorehabilitation approach for improving paretic arm func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 62 publications
(85 reference statements)
0
35
0
4
Order By: Relevance
“…A recent study reported a time-dependent effect in stroke patients. The group that received tDCS before motor training exhibited better recovery of daily functions than the group with simultaneous tDCS application [21]. In another study involving stroke patients, the 20-min tDCS before physical exercise increased muscle strength and reduced upper limb motor dysfunction [52].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…A recent study reported a time-dependent effect in stroke patients. The group that received tDCS before motor training exhibited better recovery of daily functions than the group with simultaneous tDCS application [21]. In another study involving stroke patients, the 20-min tDCS before physical exercise increased muscle strength and reduced upper limb motor dysfunction [52].…”
Section: Discussionmentioning
confidence: 93%
“…Our findings are consistent with previous studies. In a recent randomized controlled trial, which explored the time-dependent effects of tDCS on upper limb function using mirror therapy in patients with chronic stroke, tDCS before training improved daily function and kinematics compared with the concurrent stimulation [21]. In other studies investigating the time-dependent effects in healthy participants, the cortical excitability was enhanced when tDCS was applied before motor training [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, tDCS-induced plasticity is highly dependent on the state of the subject during stimulation. Liao et al ( 42 ) showed that tDCS both before and during mirror therapy resulted in better motor function than tDCS alone among chronic stroke patients. However, studies comparing the effects of tDCS alone and concurrent or sequential use of tDCS and cognitive training are scarce so far, and future studies are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing accepted procedures in administering tDCS should lead to individualized dose-controlled treatments [98]. Further, standardizing tDCS protocols for chronic stroke intervention must include when and duration of the anodal and cathodal stimulation combinations [106]. Questions on the optimal stimulation time are still being debated.…”
Section: Looking Forwardmentioning
confidence: 99%